(untitled) - Kline, Suzy; Remkiewicz, Frank (New York, 1995)
Spring becomes a memorable time for Miss Mackle's second-grade classroom because of the antics of Horrible Harry and the special insights of shy Song Lee.
Reprint. Originally published: New York : Viking, 1993.
"Ages 7-10"--Cover p. [4].